DIGITIZATION OF INFORMATION RESOURCES IN ACADEMIC LIBRARIES IN NIGERIA: CHALLENGES AND STRATEGIES (NAU Journal of Library and Information Science, 2022)
Digitization is simply the process of converting information in print format into a machine-readable form. Digitization improves access to information resources. This paper discussed the concept of digitization and information resources, benefits of digitization of information resources, skills and competencies required for digitization of library resources, and the digitization process. Challenges involved in the process of digitization of information resources in academic libraries were also highlighted. Major constraints in the digitization process include lack of ICT infrastructure, high cost of digitization equipment, poor funding, shortage of technical staff, sustainability/maintenance problems as well as legal/copyright issues. This paper established that strategies that could be adopted to enhance digitization of library resources include provision of infrastructural facilities; improved funding, trained manpower, inclusion of digitization skills in library education and maintaining standard policy protection in line with global practices.
Keywords: Digitization; Information Resources; Academic Libraries; ICT